Keratitis-ichthyosis-deafness syndrome with heterozygous p.D50N in the GJB2 gene in two Serbian adult patients - Kalezić T; Vuković I; Stojković M; Stanojlović S; Karanović J; Brajušković G; Savić-Pavićević D (Balkan Journal of Medical Genetics, 2023)
Keratitis-ichthyosis-deafness (KID) syndrome is a rare congenital ectodermal dysplastic syndrome presenting with keratitis, ichthyosis and sensorineural hearing loss. The most common causes of KID syndrome are heterozygous missense mutations in the GJB2 gene that codes for connexin 26.